Money and central bank digital currency - Sayuri Shirai (Asian Development Bank Institute (ADBI), 2019)
This paper takes an overview of the concepts and features of central bank money and private sector money and focuses on the actual performance of these types of money in selected advanced and emerging economies. In addition, digital coins (crypto assets), such as bitcoin, are newly emerged private sector money. Much attention has been given to digital coins because the underlying distributed ledge technology (DLT) enables a decentralized verification process while maintaining features similar to cash. Some central banks have expressed unease about these digital coins because of the high volatility in their values. However, the size of the newly emerged private sector money currently remains limited due to its limited use as a payment tool. Thus, it is likely to take time before digital coins are a threat to commercial banks and central banks. Meanwhile, some central banks have examined the potential application of DLT and the issuing of their own digital coins to the general public or financial institutions - the so-called "central bank digital currency" initiatives. So far, no central banks have found strong advantages of the initiatives because of several technical constraints. Given that technology has been progressing quickly, however, it is possible that central banks may increase their interest in the central bank digital currency proposals based on DLT and consider actual implementation in the near future. Meanwhile, Sweden's Riksbank has initiated a separate move by considering the issuance of deposit accounts and prepaid payment methods to the general public in the face of declining cash use. Other central banks have shown little interest in the Swedish initiative because of the potential adverse impacts on the banking system caused by a shift in retail deposits from commercial banks to the central bank.
Keywords: E42; E44; E51; 330; money; central bank digital currency; cash; digital coins; bank deposits